2016
DOI: 10.1371/journal.pone.0161364
|View full text |Cite
|
Sign up to set email alerts
|

5-ALA Fluorescence in Native Pituitary Adenoma Cell Lines: Resection Control and Basis for Photodynamic Therapy (PDT)?

Abstract: Objective: Pituitary adenomas (PA), especially invasive ones, are often not completely resectable. Usage of 5-aminolevulinic acid (5-ALA) for fluorescence guided surgery could improve the rate of total resection and, additionally, open the doors for photodynamic therapy (PDT) in case of unresectable or partially resected PAs. The aim of this study was to investigate the uptake of 5-ALA and the effect of 5-ALA based PDT in cell lines. Methods: GH3 and AtT-20 cell lines were incubated with different concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…After 24 h of incubation with 5-ALA, the cells exhibited up to 21-fold higher NIR autofluorescence. This indicated that HeLa cells actively metabolized 5-ALA and likely accumulated the produced fluorescent PPIX (Figure 1), as observed in cancer cell lines (Krieg et al, 2002; Nemes et al, 2016). After normalization of NIR FP fluorescence to the increased autofluorescence we found that the real effective brightness of all NIR FPs has not changed and remained the same as without 5-ALA (Figure 3b).…”
Section: Resultsmentioning
confidence: 61%
“…After 24 h of incubation with 5-ALA, the cells exhibited up to 21-fold higher NIR autofluorescence. This indicated that HeLa cells actively metabolized 5-ALA and likely accumulated the produced fluorescent PPIX (Figure 1), as observed in cancer cell lines (Krieg et al, 2002; Nemes et al, 2016). After normalization of NIR FP fluorescence to the increased autofluorescence we found that the real effective brightness of all NIR FPs has not changed and remained the same as without 5-ALA (Figure 3b).…”
Section: Resultsmentioning
confidence: 61%
“…Notably, it has been also demonstrated that BK Ca channels are functionally expressed in either retinal pigment epithelial cells, vascular endothelial cells, or amniotic fluid-derived stem cells (Li et al, 2000; Schmidt-Erfurth and Hasan, 2000; Sheu et al, 2005; Hua et al, 2014; Hu et al, 2015; Liu et al, 2015, 2018, 2019a,b). Taking this into account, to what extent VP-induced changes in BK Ca -channel activity existing in these cells are intimately connected with its actions on sensory retina or pituitary adenoma during photodynamic therapy (Marks et al, 2000; Rahimipour et al, 2003; Rosenblatt et al, 2005; Hu et al, 2015; Nemes et al, 2016; Liu et al, 2018; Min et al, 2018; Iacono et al, 2019) remains to be imperatively investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Upon cell exposure to VP particularly along with long-term light exposure, the reactive oxygen species would be excessively produced, and resultant byproducts of oxidative metabolism can then interact with membrane phospholipids and proteins that constitute ion transport pathways such as BK Ca channels. Lastly, It will be worthy of being investigated regarding to what extent VP-mediated modifications on membrane ion channels reported herein is closely linked to the inhibition of VAP-TEAD complex followed by changes in proliferation or differentiation of different types of neoplastic or stem cells, given that the fact that such photosensitizers as sensitized photochemical modification in an array of tumors, including pituitary tumors and gliomas, have been widely utilized (Marks et al, 2000; Brown et al, 2004; Solban et al, 2006; Triesscheijn et al, 2006; Cole et al, 2008; Brodowska et al, 2014; Valero et al, 2015; Morishita et al, 2016; Nemes et al, 2016; Chen and Hu, 2017; Baskaran et al, 2018; Liao et al, 2018; Mulder et al, 2018; Chen et al, 2019; Li et al, 2019; Pellosi et al, 2019; Qin et al, 2019; Zhang et al, 2019). Alternatively, the efficacy of VP in inhibiting YAP/TEAD interaction was currently noted to remain debated (Lui et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A signi cant down-regulation of Fech expression was found in several malignancies [25][26][27][28], resulting in PpIX accumulation in such tumor cells. Indeed, accumulated PpIX in tumor cells leads to photodynamic therapy as effective adjuvant therapy for treating various cancers through visualizing the extent and margins of tumors, including PA [29].…”
Section: Relationship Between Involved Genes In Triplet Fech {Safb Cdk9}mentioning
confidence: 99%